ACE-2, TMPRSS2 and Beyond; Promising Targets and Tools for COVID-19 Prophylaxis and Treatment - Akçahan GEPDİREMEN; Meltem KUMAŞ (Bezmiâlem Science, 2020)

(untitled)
Several repurposing drugs and ongoing vaccine researches to combat Coronavirus Disease-19 (COVID-19) are testing clinically, worldwide. COVID-19 caused by severe acute respiratory failure syndrome-CoV-2, uses angiotensin-converting enzyme 2 (ACE-2) as a functional receptor for entry into the cells, followed by its priming by transmembrane protease serine 2 (TMPRSS2). Most of the ACE-2 expressing cells are alveolar type II pneumocytes. Viral S-glycoprotein, TMPRSS2 and ACE-2 inhibition, as extracellular media components, are potential targets of future therapy. ACE-2 and/or TMPRSS2 blockade is thought to be beneficial in the prevention or treating of this infection which will be the most convenient for pharmacoeconomics and effectiveness, regarding similar future pandemics. Despite substrate-based design and synthesis of ACE-2 inhibitor compounds were presented almost two decades ago, data on renin angiotensin system activation or its blockers, especially ACE-2, are limited by now. Priority must be given to design a convenient vaccine soon, but due to the high mutation ability of such viruses mean that new vaccines may need to be developed for each outbreak. So, de novo drugs such as ACE-2 or TMPRSS2 blockers need to be developed which can specifically block spike binding sites of the target cells and prevent virus intrusion, especially at the extracellular media, for future pandemics.